StoryTime - Adams, Georgie; Brol, Magda (London : Zephyr, 2019)
Doogle the dinosaur, Buttons the bear and Cabbage the cat live in Storyland where stories grow on the story tree. One night a storm blows them all away. Join the three friends to find a wicked witch, a dragon with a sweet tooth, bouncing bed bugs, a lonely giant, a frightened ghost, aliens... to name a few, and bring them back safely. This is a top quality collection of magical and familiar everyday stories which tap into early learning skills and will become a family favourite. You can spend as much time as you like in Storyland. Mix and match easy-to-spot leaf symbols to decide how long.
First published in 2019.
Keywords: Animals -- Juvenile fiction; Short stories; Picture books